2012
DOI: 10.17796/jcpd.36.4.n444r730r773un53
|View full text |Cite
|
Sign up to set email alerts
|

Caries-Preventive Effect of Fissure Sealant Containing Surface Reaction-Type Pre-reacted Glass Ionomer Filler and Bonded by Self-etching Primer

Abstract: Objective: We aimed to evaluate the caries-preventive effect of a fissure sealant containing surface reactiontype pre-reacted glass ionomer (S-PRG) filler and bonded by self-etching primer versus those of 2 conventional resin-based sealants bonded by acid etching in terms of its impact on enamel demineralization and remineralization, enamel bond strength, and integrity of debonded enamel surfaces. Materials and method: Demineralization, remineralization, and bond strength on untreated enamel and enamel subsurf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 18 publications
1
24
0
1
Order By: Relevance
“…Since the direct bonding of orthodontic brackets to enamel was introduced by Newman 2) in the mid 1960s, acid-etching of enamel surfaces for bracket bonding procedures has been accepted in clinical orthodontics 3) . Also, pit-and-fissure sealant using resinbased materials that require an acid-etching process has been accepted to prevent occlusal caries in pediatric dentistry 4) . A previous in vitro study 5) showed that the mechanical properties of the enamel surface region were decreased by etching-based bracket bonding, and irreversible alteration of the enamel might increase the risk of enamel micro cracks during debonding procedures.…”
Section: An Acid-etching Technique Was Introduced In the 1950smentioning
confidence: 99%
“…Since the direct bonding of orthodontic brackets to enamel was introduced by Newman 2) in the mid 1960s, acid-etching of enamel surfaces for bracket bonding procedures has been accepted in clinical orthodontics 3) . Also, pit-and-fissure sealant using resinbased materials that require an acid-etching process has been accepted to prevent occlusal caries in pediatric dentistry 4) . A previous in vitro study 5) showed that the mechanical properties of the enamel surface region were decreased by etching-based bracket bonding, and irreversible alteration of the enamel might increase the risk of enamel micro cracks during debonding procedures.…”
Section: An Acid-etching Technique Was Introduced In the 1950smentioning
confidence: 99%
“…The crystal structure of the enamel surface may change from hydroxyapatite to fluorapatite with laser irradiation and fluoride application. 4. The values of MD, hardness, and elastic modulus of the enamel surface after immersion in demineralization solution were correlated.…”
Section: Discussionmentioning
confidence: 99%
“…The acids produced by bacteria in the oral environment cause the demineralization of the enamel. The enamel of an immature tooth and around an orthodontic bracket is at extremely high risk of demineralization 3,4) . Because fluoride plays an important role in preventing demineralization, fluoride-containing products, such as toothpastes, mouth rinses, pit-and-fissure sealants, and fluoride-releasing adhesives, have been used widely clinically [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These multiple ions eluted from some S-PRG filler-containing dental materials have various bioactive effects, such as strengthening of the tooth structure [16][17][18] , anti-plaque effect 19,20) , dentin remineralization [21][22][23] , acid-buffering capacity 15,24) , and inhibition of enzymatic activity of periodontopathic bacteria 25,26) . However, no studies have addressed the bioactive effect of mouthguards containing the S-PRG filler.…”
Section: Introductionmentioning
confidence: 99%